Analisis Semiotika Bias Gender dalam Film Ngeri-Ngeri Sedap (Karya Bene Dion Raja Gukguk) - Bangun, Dinda Almunawaroh; Azhar, Anang Anas (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Current Gender issues have not shown equality. Inequality between women and men almost occurs in all fields such as education, politics and even family. Film is a representation of the form of human daily life, both based on true stories and science fiction from writers or directors. This study uses descriptive qualitative methodology by identifying and interpreting myths, denotations, and indicators of Gender inequality in films.. Researchers found three scenes in the film "Ngeri-Ngeri Sedap" that depicted Gender bias. These scenes were analyzed using Roland Barthes' semiotics to uncover denotations, connotations, and myths, aiming to analyze Gender bias in Bene Dion's film Raja Gukguk. The film highlights male dominance inside and outside the family, showing how men make decisions without considering the well-being of their families. Taken together, the study reveals the deep-rooted Gender bias depicted in the film.